Dinucleotide-sensing proteins: linking signaling networks and regulating transcription. - Lamb, H; Stammers, D; Hawkins, A (2008)
Differential binding of dinucleotides to key regulatory proteins can modulate their interactions with other proteins and, in some cases, can signal fluctuations in the cellular redox state, to produce changes in transcription and physiological state. The dinucleotide-binding proteins human HSCARG and yeast transcription repressor Gal80p are examples that offer exciting glimpses into the potential for dinucleotide-sensing proteins to couple fluctuations in dinucleotide ratios to changes in transcription and to act as networking agents linking different classes of signaling molecules.